2019
DOI: 10.3390/ijerph16173041
|View full text |Cite
|
Sign up to set email alerts
|

Translating Urban Walkability Initiatives for Older Adults in Rural and Under-Resourced Communities

Abstract: The built environment can promote physical activity in older adults by increasing neighborhood walkability. While efforts to increase walkability are common in urban communities, there is limited data related to effective implementation in rural communities. This is problematic, as older adults make up a significant portion of rural inhabitants and exhibit lower levels of physical activity. Translating lessons from urban strategies may be necessary to address this disparity. This review examines best practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Rural adults may face more barriers with finding safe, accessible locations to walk (e.g., pedestrian-friendly space, sidewalks). 42,43 Additionally, differences in how physical activity was measured may explain some of this variation among the literature; subjective, self-reported measures of physical activity may under or overestimate physical activity compared to objective, pedometer-based assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rural adults may face more barriers with finding safe, accessible locations to walk (e.g., pedestrian-friendly space, sidewalks). 42,43 Additionally, differences in how physical activity was measured may explain some of this variation among the literature; subjective, self-reported measures of physical activity may under or overestimate physical activity compared to objective, pedometer-based assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the walkability of one's environment may help explain why rural individuals did not achieve similar levels of physical activity compared to their urban counterparts. Rural adults may face more barriers with finding safe, accessible locations to walk (e.g., pedestrian‐friendly green space, sidewalks) 42,43 . Additionally, differences in how physical activity was measured may explain some of this variation among the literature; subjective, self‐reported measures of physical activity may under or overestimate physical activity compared to objective, pedometer‐based assessments.…”
Section: Discussionmentioning
confidence: 99%
“…There is no dearth of reviews on walkability as reported by Ewing et al in 2015. Since then, a multitude of reviews have emerged discussing varied perspectives related to the built environment (Arellana et al, 2020;Bonaccorsi et al, 2020;Dadpour et al, 2016;Elzeni et al, 2022;Fonseca et al, 2022;Hassen & Kaufman, 2016;Jamei et al, 2021;Nasrollahi et al, 2020;Salvo et al, 2018;Smith et al, 2017;Wang & Yang, 2019;Westenhöfer et al, 2023;Yun, 2019), health and well-being (Baobeid et al, 2021;Bonaccorsi et al, 2020;Klann et al, 2019;Nasrollahi et al, 2020;Salvo et al, 2018;Smith et al, 2017;Wang & Yang, 2019;Westenhöfer et al, 2023), social factors (Bonaccorsi et al, 2020;Dadpour et al, 2016;Hassen & Kaufman, 2016;Herrmann-Lunecke et al, 2020;Iroz-Elardo et al, 2021;Klann et al, 2019;Salvo et al, 2018), context (Jamei et al, 2021;Klann et al, 2019), evaluation tools (Arellana et al, 2020;Blečić et al, 2020;Dragović et al, 2023;Wang & Yang, 2019) and sustainability (Baobeid et al, 2021;Herrmann-Lunecke et al, 2020;Nasrollahi et al, 2020). Pedestrian experience (Arellana et al, 2...…”
Section: Introductionmentioning
confidence: 99%
“…Communities may better support older adult physical activity and community walkability by providing microscale improvements (i.e. maintenance footpaths, street lights, sidewalks/protected walkways, and rest stops/benches), and larger scale permanent infrastructure, such as municipal parks and recreational facilities (Klann, et al, 2019). In many communities, parks have been shown to increase walkability of the community and ultimately overall physical activity level (Siu, et al, 2012;Todd, et al, 2016;Salvo, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%